SiPP (Stroke in Pregnancy and Postpartum): A prospective, observational, international, multicentre study on pathophysiological mechanisms, clinical profile, management and outcome of cerebrovascular diseases in pregnant and postpartum women. (June 2020) - Lorenzano, Svetlana; Kremer, Christine; Pavlovic, Aleksandra; Jovanovic, Dejana R; Sandset, Else Charlotte; Christensen, Hanne; Bushnell, Cheryl; Arsovska, Anita; Sprigg, Nikola; Roffe, Christine; Ijäs, Petra; Gdovinova, Zuzana; et al.
Rationale: Cerebrovascular diseases associated with pregnancy and postpartum period are uncommon; however, they can have an important impact on health of both women and foetus or newborn. Aims: To evaluate the frequency, characteristics and management of cerebrovascular events in pregnant/postpartum women, to clarify pathophysiological mechanisms underlying the occurrence of these events including biomolecular aspects, and to assess the short- and long-term cerebrovascular and global cardiovascular outcome of these patients, their predictors and infant outcome. Methods and design: This is an observational, prospective, multicentre, international case–control study. The study will include patients with cerebrovascular events during pregnancy and/or within six months after delivery. For each included case, two controls will be prospectively recruited: one pregnant or puerperal subject without any history of cerebrovascular event and one non-pregnant or non-puerperal subject with a recent cerebrovascular event. All controls will be matched by age, ethnicity and type of cerebrovascular event with their assigned cases. The pregnant controls will be matched also by pregnancy weeks/trimester. Follow-up will last 24 months for the mother and 12 months for the infant. Summary: To better understand causes and outcomes of uncommon conditions like pregnancy/postpartum-related cerebrovascular events, the development of multisite, multidisciplinary registry-based studies, such as the Stroke in Pregnancy and Postpartum study, is needed in order to collect an adequate number of patients, draw reliable conclusions and give definite recommendations on their management.